1997
DOI: 10.1046/j.1365-2567.1997.d01-2341.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of B‐cell receptor engagement on CD40‐stimulated B cells

Abstract: SUMMARYActivation of human B cells in vitro either by cross-linking of surface immunoglobulins (sIg) or by triggering CD40 antigen, in the presence of interleukin-10 (IL-10) and interleukin-2 (IL-2), may result in high levels of immunoglobulin secretion in vitro. We studied the combined effects of ligation of the B-cell receptor (BCR) and CD40 [with anti-CD40 monoclonal antibody (mAb)] on B-cell proliferation and production of human immunoglobulin. For this purpose highly purified splenic B cells were cultured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Following exposure to CD40L plus anti-IgM Ab (or pansorbin) for 7 days, B lymphocytes become activated, proliferate, and differentiate, thus increasing their production of IgM and IgG (20). Our findings of drastically reduced IgM and IgG levels following incubation with indomethacin or the selective Cox-2 inhibitor SC-58125 supports the concept that the B cell Cox-2-derived products are required for optimal Ab production.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Following exposure to CD40L plus anti-IgM Ab (or pansorbin) for 7 days, B lymphocytes become activated, proliferate, and differentiate, thus increasing their production of IgM and IgG (20). Our findings of drastically reduced IgM and IgG levels following incubation with indomethacin or the selective Cox-2 inhibitor SC-58125 supports the concept that the B cell Cox-2-derived products are required for optimal Ab production.…”
Section: Discussionsupporting
confidence: 71%
“…Pharmacological doses of these drugs that have been previously shown to block PG production range from 5 to 40 M (9, 10). Dose response experiments (1,5,10,20,40, and 80 ⌴) were conducted to determine the optimal dose for PG inhibition using the supplier's protocol for the PG screening kit (Cayman Chemical).…”
Section: Small Molecule Cox Inhibitorsmentioning
confidence: 99%
“…The varied effects of the different anti-Ig mAbs on cell division suggested that these reagents might differ qualitatively in their ability to signal via sIg. Different mitogenic properties of various anti-Ig reagents have been noted previously and attributed to qualitatively different signals delivered to the B cell as a result of different sIg cross-linking capacities (18,(51)(52)(53), their binding of different sIg epitopes (53,54), or coligation of Fc␥RIIb (55,56). This latter possibility was eliminated in this study by the inclusion of an antiFc␥RIIb mAb in selected experiments.…”
Section: Discussionmentioning
confidence: 63%
“…It is known that cytokines play a critical role in immunoglobulin class switching. Schilizzi et al have shown that simultaneous B-cell antigen receptor cross-linking along with CD40 engagement in the presence of IL-10 or IL-4 reduced IgG secretion in vitro (43). Thus, the decreased IgMto-IgG switch could presumably be explained by the high levels of IL-4 and IL-10 induced by CD40L SIV VLPs combined with CD40-CD40L interactions.…”
Section: Discussionmentioning
confidence: 99%